Validity and reliability of an android device for the assessment of fall risk in older adult inmates - Enrique J. Vera‐Remartínez; Rocío Lázaro‐Monge; Sofía V. Casado‐Hoces; Elena Garcés‐Pina; María Pilar Molés‐Julio (Wiley, 2023)
Abstract Aim To validate the Android device, FallSkip, as a tool to assess the fallers in older adult inmates. Design A cross‐sectional descriptive and analytical study. Methods For the validation of the FallSkip, the diagnostic criterion used was the risk of having suffered a fall during the last year. Results The results for the FallSkip tool were as follows: sensitivity 60.7%; specificity 83.0%; positive predictive value 65.4%; negative predictive value 80.0%; accuracy 75.3%. In total, 32.1% of participants were found to be at high risk of falls, 23.5% were at mild risk and 7.4% were found to have no risk. Conclusion The FallSkip device is shown to be a very suitable tool for fall risk assessment. The sample studied presented a statistically significant percentage of fall risk, which made it necessary to carry out interventions through physical activities to improve balance and stability.